La reconstrucció virtual de dos escenaris litúrgics medievals: els absis majors de les catedrals romàniques de Vic i de Girona = The virtual reconstruction of two medieval liturgical settings: The main apses of the Romanesque cathedrals of Vic and Girona - Jubany, Marc Sureda i (Miscel·lània litúrgica catalana, 2023)
Over the course of the years 2021-2022, the main apses of the Romanesque cathedrals of Vic and Girona, both of which had disappeared as a result of the reconstruction of the respective buildings, have been digitally rebuilt. In both cases, the purpose of the reconstructions, apart from generating the respective cultural products, was to carry out a scientific reflection on the altar arts and the spatial and decorative configuration of the liturgical settings in the context of Catalan Romanesque art (11th-13th centuries), through the study of these specific spaces and of the various possibilities of reconstruction based on the available data, together with a critical discussion of these matters.